The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1080/00480169.2015.1037813
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with fetal losses in ewe lambs on a New Zealand sheep farm

Abstract: Low pre-mating weight and/or low weight gain from mating to pregnancy diagnosis was associated with increased fetal loss, emphasising the importance of ewe lambs achieving target pre-mating weights and liveweight gains during pregnancy. Infection with Leptospira serovar Pomona was associated with fetal loss in the 2012-born cohort and the possibility of infection with this serovar should be considered when investigating cases of fetal loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 14 publications
2
26
0
Order By: Relevance
“…The presence of antibodies against the serogroup Pomona was previously reported in sheep from slaughterhouses (Caffarena, Cacchione, Cascelli, & Martínez, ) and in cattle (Zarantonelli et al., ) in Uruguay. Furthermore, Pomona serogroup strains have been implicated in clinical disease in lambs in other countries (Davidson & Hirsh, ; Ellis et al., ; Leon‐Vizcaino et al., ; Ridler et al., ; Vermunt et al., ,b). In our study, we isolated for the first time two strains of L. interrogans serogroup Pomona serovar Kennewicki from naturally infected sheep.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of antibodies against the serogroup Pomona was previously reported in sheep from slaughterhouses (Caffarena, Cacchione, Cascelli, & Martínez, ) and in cattle (Zarantonelli et al., ) in Uruguay. Furthermore, Pomona serogroup strains have been implicated in clinical disease in lambs in other countries (Davidson & Hirsh, ; Ellis et al., ; Leon‐Vizcaino et al., ; Ridler et al., ; Vermunt et al., ,b). In our study, we isolated for the first time two strains of L. interrogans serogroup Pomona serovar Kennewicki from naturally infected sheep.…”
Section: Discussionmentioning
confidence: 99%
“…serogroups Pomona, Grippotyphosa and Sejroe (serovar Hardjo) were isolated from ovine fetuses, suggesting a possible role of these serogroups in sheep abortion (Ellis, Bryson, Neill, McParland, & Malone, ; Leon‐Vizcaino, Hermoso de Mendoza, & Garrido, ). Fetal losses have also been found to be associated with seroreactivity to serogroup Pomona (Ridler, Vallee, Corner, Kenyon, & Heuer, ).…”
Section: Introductionmentioning
confidence: 99%
“…A proportion of 0.75 was used to simulate foetal loss due to Pomona in Pomona seropositive ewes (Ridler et al, ). At the population level, this kind of abortion outbreak due to Pomona was thought to be a rare event.…”
Section: Methodsmentioning
confidence: 99%
“…In New Zealand, seropositivity to Leptospira borgpetersenii serovar Hardjo (Hardjo‐bovis) and Leptospira interrogans serovar Pomona (Pomona) is highly prevalent in beef cattle, sheep and deer (Ayanegui‐Alcerreca et al, ; Dreyfus et al, ). Additionally, foetal loss was associated with Hardjo‐bovis and Pomona seropositivity in beef cattle (Sanhueza, Heuer, & West, ), and Pomona seropositivity in one sheep farm (Ridler, Vallee, Corner, Kenyon, & Heuer, ). Furthermore, vaccination trials in deer suggested an economic benefit of immunization against leptospirosis due to increased growth rate and weaning percentage (Subharat, Wilson, Heuer, & Collins‐Emerson, , ).…”
Section: Introductionmentioning
confidence: 99%
“…However, there are several challenges for the maintenance of reproductive efficiency, with handling infectious diseases being key among them. Leptospirosis is a significant zoonotic bacterial disease (ALLAN et al, 2018;COSTA et al, 2015), which has been associated with reproductive failure and economic losses in sheep (RIDLER et al, 2015).…”
Section: Introductionmentioning
confidence: 99%